Decision Making and Communication About Child Spacing Among Somali Couples in Minnesota. Issue 2 (12th April 2019) - Cox, Carie Muntifering; Ahmed, Fathi; Mitchell, Ashley; Ganey, Abdillahi; Kahin, Adar; Kahin, Abdillahi
Abstract : CONTEXT: Since civil unrest broke out in Somalia in the 1990s, large numbers of Somalis have immigrated to Western countries, including the United States. It is unknown whether these immigrants maintain their cultural norms of low contraceptive use and high fertility when they live in settings with different norms . METHODS: In 2016, interviews were conducted in Minnesota with Somali immigrants and refugees to explore couple communication and decision making regarding child spacing. Nineteen married men and women aged 25–51 were interviewed. After a coding scheme was developed, key themes were identified and examined by participants' sex, number of children and age of arrival in the United States . RESULTS: Most participants discussed child spacing with their spouse and had positive or neutral experiences. Some participants, especially those with multiple children, stated that living in their new country had influenced their fertility desires. Only those who had arrived after the age of 20 mentioned that experiencing closely spaced births had motivated them to discuss child spacing. Participants emphasized the importance of information sharing, compromise and joint decision making with their spouse. Priority for child‐spacing decision making was granted to women, largely because of their primary role in childbirth. Men who had arrived in the United States before turning 20 were more definitive about giving women decision‐making priority . CONCLUSIONS: These findings provide insight into how Somali immigrant and refugee couples communicate and make decisions about child spacing, and may be helpful in informing the development of culturally specific reproductive health programs .